2001
DOI: 10.1152/jappl.2001.90.6.2212
|View full text |Cite
|
Sign up to set email alerts
|

Is the V˙o 2 slow component dependent on progressive recruitment of fast-twitch fibers in trained runners?

Abstract: The goal of this study was to use spectral analysis of EMG data to test the hypothesis that the O2 uptake VO2) slow component is due to a recruitment of fast fibers. Thirteen runners carried out a treadmill test with a constant speed, corresponding to 95% of the velocity associated with maximal VO2. The VO2 response was fit with the classical model including three exponential functions. Electrical activity of six lower limb muscles (vastus lateralis, soleus, and gastrocnemius of both sides) was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
115
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 60 publications
14
115
2
5
Order By: Relevance
“…The change in MPF depends on the functional role of the muscle and various factors may change the MPF. This result diŠers from that of a previous study by Borrani et al (2001), who observed an increase in MPF during prolonged pedalling exercise. They hypothesized that slow-twitch MUs recruited at the beginning of the exercise are unable to sustain the work rate, requiring progressive recruitment of low-e‹ciency type IIˆbres.…”
Section: Discussioncontrasting
confidence: 99%
“…The change in MPF depends on the functional role of the muscle and various factors may change the MPF. This result diŠers from that of a previous study by Borrani et al (2001), who observed an increase in MPF during prolonged pedalling exercise. They hypothesized that slow-twitch MUs recruited at the beginning of the exercise are unable to sustain the work rate, requiring progressive recruitment of low-e‹ciency type IIˆbres.…”
Section: Discussioncontrasting
confidence: 99%
“…Although no specific analysis of muscular parameters has been conducted in the current investigation, the change in neuromuscular activity of peripheral skeletal muscles remains an attractive hypothesis to explain the decrement in running performance after the VI ride. Selected lower extremity muscles such as rectus femoris, vastus lateralis, vastus medialis and soleus have been reported to be substantially recruited during cycling (Citterio and Agostini 1984;Marsh and Martin 1995;Takaishi et al 1996) and running (Bijker et al 2002;Borrani et al 2001), suggesting that any changes in recruitment of these muscles during prior cycling may affect running performance. During isolated cycling exercises, an increased activity of quadriceps and soleus muscles (from the EMG method) has been observed with increasing PO in a non-fatigued state (Citterio et Agostini 1984;Marsh and Martin 1995;Takaishi et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Borrani et al. [7] suggest that the modification of C could be related to a modification of an index of the internal cost. Therefore, in order to understand why there are significant differences in C among runners of different training status, there is a need to compare kinetic, potential, and internal energies indices in addition to the overall energy cost.…”
Section: Paragraph Numbermentioning
confidence: 99%